The Relationship between Smartphone Addiction and Insomnia in Rural Adolescents - Wahyuni, Sylvia Dwi; Azizah, Nurul; Ulfiana, Elida; Ching-lan, Lin Esther (International Journal of Psychosocial Rehabilitation, 2020)
One factor influencing insomnia in adolescents that relating to habits such as lifestyle. They use smartphones for a long time particularly to access social media, chatting, and playing games until late at night. This study aimed to determine the relationship between smartphone addiction and insomnia in adolescents. The research was descriptive correlational with a cross-sectional method. The sample in this research was identified using a purposive sampling technique with 103 samples with the following criteria: 1) 16 to 18 years old, 2) using a smartphone, and 3) able to communicate well. The independent variable in this study was smartphone addiction and the dependent variable was insomnia. The instruments of this research were smartphone addiction and the Kelompok Studi Psikiatri Biologi Jakarta insomnia rating scale (KSPBJ-IRS) questionnaire. This research undertook statistical analysis using the Spearman Rank test with a significance level α=0.05. The results of the statistical test gave a p value=0.006, and the r value=0.267. There was a correlation between smartphone addiction with insomnia in adolescents. Moreover, the significant aspects of addiction were salience and relapse. Support from parents, counseling teachers and community nurses can help students reduce smartphone use especially during sleep and can manage sleep so that students can overcome insomnia.